Assessment of genetic improvements in wheat yield and nitrogen use efficiency under different nitrogen input levels: A global perspective - Huang, Tiantian; Sun, Ruiqi; Wu, Qianxiang; Zhang, Xintong; Li, Jiaquan; Zhou, Bowei; Liao, Yuncheng; Qin, Xiaoliang; Reynolds, Matthew P.; Siddique, Kadambot H.M. (Elsevier B.V., 2025)
Wheat breeding programs have enhanced yield and nitrogen use efficiency (NUE). However, modern breeding—often conducted under optimal growth conditions such as high nitrogen fertility—may reduce the adaptability of new cultivars to less favorable environments. This study assesses genetic improvements in wheat yield and NUE under varying nitrogen fertilization levels. Wheat breeding has improved the yield potential of modern cultivars under high (HN; ≥180 kg ha–1), medium (MN; 100–180 kg ha–1), and low (LN; 0–100 kg ha–1) nitrogen conditions. However, a pivotal shift occurred around 2000: while yields continued to increase under HN conditions, they stagnated or declined under LN and MN. The greater genetic gains in yield under HN are primarily attributed to the higher genetic gains in harvest index under HN compared to LN and MN. Over time, the annual genetic gain in NUE increased under all nitrogen conditions: 0.47 % for LN, 0.41 % for MN, and 0.59 % for HN. The contribution of nitrogen uptake efficiency (NUpE) and nitrogen utilization efficiency (NUtE) to NUE may be related to nitrogen application rate: NUtE contributes more under HN, while NUpE contributes more under MN and LN. While breeding has enhanced wheat yield and NUE, these improvements have been less pronounced under LN conditions, limiting the adaptability of modern cultivars to suboptimal environments.